-3(y-3)=-7y+17

Simple and best practice solution for -3(y-3)=-7y+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(y-3)=-7y+17 equation:



-3(y-3)=-7y+17
We move all terms to the left:
-3(y-3)-(-7y+17)=0
We multiply parentheses
-3y-(-7y+17)+9=0
We get rid of parentheses
-3y+7y-17+9=0
We add all the numbers together, and all the variables
4y-8=0
We move all terms containing y to the left, all other terms to the right
4y=8
y=8/4
y=2

See similar equations:

| x+4x+14=244 | | X+2x-11=23 | | y+(–10)=6 | | 3n+1=33 | | 2(5-x)=25-2(3x-0,5) | | 4+3x=2x-7 | | 3(×-6)=2(x+6) | | 13x-11=2x | | 4x-5=9+6x | | 3*x+2=4 | | 100y+70+0=114y | | 2m-5m=-7+9 | | 3m^2-12m-20=0 | | R*2-21r+80=0 | | 65=(3a-2)*a | | 2m-7=5m-9 | | 50+x=11x | | x/5+7=x/3 | | 0.3+1p=75 | | 8t-10=3(6-2t) | | 8x-28-40-8x=6x+12-5x+35 | | 2000-x=3x | | 296=3.14r25 | | -7*(2-3x)=56 | | 48x-533=265 | | -1/2x+1=15 | | 4x+9=6x+11 | | 13b-7=3b+13 | | -1/2x+1=15x1/2 | | 6x+8/4x-3=2 | | X^3+100x+25=0 | | 2/3t=-4 |

Equations solver categories